2020
DOI: 10.1021/acs.langmuir.0c00217
|View full text |Cite
|
Sign up to set email alerts
|

Subpatterns of Thin-Sheet Splash on a Smooth Surface

Abstract: When a droplet impacts a smooth solid surface with a sufficiently high inertia, a thin sheet is created and the whole droplet fluid then breaks apart. Thin-sheet creation and threshold pressures in drop splashingLatkaA. Latka, A. Soft Matter201713740747 defined it as thin-sheet splash. In this work, we used a high-speed camera with a long-distance microscope and experimentally showed that thin-sheet splash can be subdivided into three distinct patterns in terms of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Similarly, high- Oh liquids (75 and 85% glycerol solutions) only breakup within the retracting process. Remarkably, the liquid films develop outwardly and upwarp in a certain angle with surfaces for all splashing cases, where thin gas films are wedged. ,, In addition, the wedged angle becomes smaller with increasing liquid viscosity …”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Similarly, high- Oh liquids (75 and 85% glycerol solutions) only breakup within the retracting process. Remarkably, the liquid films develop outwardly and upwarp in a certain angle with surfaces for all splashing cases, where thin gas films are wedged. ,, In addition, the wedged angle becomes smaller with increasing liquid viscosity …”
Section: Resultsmentioning
confidence: 92%
“…Hereto, two distinct patterns of droplet splash are observed clearly by identifying that the disintegration of the liquid film occurs at different stages. Previous experimental studies ,,,,, have shown that the film disintegration is a key indicator for the disintegration of an impacting drop. For low-viscosity liquids, the splash is characterized by the separation of at least one secondary droplet from the rim of the spreading liquid film.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21,[54][55][56] Different splashing patterns can be distinguished as the liquid viscosity increases. 57,58 For the more viscous liquids, a separate regime appears between deposition and corona splashing, for which the liquid sheet separates from the surface, but does not break into separate droplets. 51 Interestingly, splashing has not been observed experimentally above a viscosity of about 20 mPa s. It is not clear whether this is due to experimental limitations to reach the splashing threshold, or if it is a fundamental limit for splashing.…”
mentioning
confidence: 99%